Building The Opus – Case Study and History of a Double Curved Glazed Dubai Project - A. Koltay (Challenging Glass Conference, 2018)
The Opus project was designed by Zaha Hadid Architects, for Omniyat in Dubai. It is a 20 story fully glazed building, resembling a cube with the core melted out. The outer flat facades are neutral transparent glazed with silver mirror pattern, while the core area is dark blue 3D formed glazing. To achieve this vision, several glass processing technologies were studied, selected, specified – and some abandoned after further studies. The project implemented several newly developed technologies, pushing the limits of the industry. Challenges included achieving the 3D double curved shape, achieving the color, achieving adequate performance for Dubai climate, dealing with the radiation focusing effect the geometry imposes, ensure seamless visual appearance among different support systems – roof, wall, soffit- , procure special materials in sufficient quantities in reasonable time and keeping the project affordable. The presentation will give a summary of the project’s technical development.